KEDUDUKAN KREDITUR KONKUREN YANG MEMBATALKAN PERJANJIAN PERDAMAIAN MENURUT UNDANG - UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU (STUDI PUTUSAN NOMOR: 02/PDT.SUS-PEMBATALAN PERDAMAIAN/2020/PN.NIAGA.JKT.PST jo. PUTUSAN MAHKAMAH AGUNG NOMOR: 963 - Vincent Stanly; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2022)
In Indonesia, Bankruptcy processes became very popular since the Monetary Crisis 1998 when the Rupiah exchange rate against USD decreased at that time. As a result, many debtors fail to pay creditor debts. In connection with that, the government issued a regulation regarding Bankruptcy and now it has been regulated by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt (PKPU). The Peace Agreement process in PKPU is a form of peace between the Debtor and the Creditor. The Peace Agreement that has been legalized (homologation) by the Court will be valid and legally binding. In the case of PT Harmas Jalesveva, the Developer has been late in carrying out its obligations in accordance with the agreed time limit in the Homologation agreement so that the Applicant in this case who is registered as Concurrent Creditor submits a cancellation of the Homologation agreement. With this case, the author will discuss the Position and Legal Consequences of Concurrent Creditors who cancel the Homologation agreement. The type of research used is normative juridical research. Collecting data in this research is through descriptive qualitative.